The potential value of the use of berberine in depression: a systematic review and meta-analysis of preclinical studies - Yao, Bifang; Long, Zhengxiang; Lin, Xiaojiao; Chen, Guangqiang; Li, Xiaoyu; Ye, Ziqi; Liu, Jiahong (Frontiers in Pharmacology, 2025)
BackgroundDepression is a prevalent global disorder that imposes a significant burden on individuals worldwide. Berberine is a promising candidate for future antidepressant therapies; however, no comprehensive systematic evaluation has been conducted to date.MethodsFive electronic databases—PubMed, Embase, Web of Science, OVID, and the Cochrane Library—were systematically searched to identify preclinical studies investigating the antidepressant effects of berberine. Outcomes were assessed using the standardized mean difference with 95% confidence intervals to evaluate overall effect sizes. Study quality was evaluated using the 10-item Systematic Review Centre for Laboratory Animal Experimentation risk of bias tool. Publication bias was assessed if more than 10 studies were included in an analysis.ResultsA total of 20 preclinical studies evaluating berberine‘s antidepressant effects were identified. Berberine administration was associated with reduced depression-like behaviors. Specifically, Berberine significantly: increased body weight (n = 7; SMD = 1.67; 95% CI: 0.57 to 2.76; P < 0.00001),Reduced immobility time in the tail suspension test (n = 9; SMD = −2.41; 95% CI: −3.15 to −1.67; P = 0.01),Increased sucrose consumption (n = 12; SMD = 1.82; 95% CI: 1.29 to 2.34; P = 0.02),Reduced immobility time in the forced swim test (n = 17; SMD = −2.35; 95% CI: −2.91 to −1.79; P < 0.00001),Increased total movement distance in the open field test (n = 7; SMD = 1.70; 95% CI: 0.58 to 2.81; P < 0.00001),Increased time spent in the open field test (n = 3; SMD = 1.02; 95% CI: 0.44 to 1.60; P = 0.92), Increased the number of crossings in the open field test (n = 4; SMD = 0.76; 95% CI: 0.20 to 1.33; P = 0.23). Furthermore, berberine was found to reduce levels of inflammatory markers, enhance neurotransmitter levels (excluding dopamine), and elevate brain-derived neurotrophic factor levels.ConclusionBerberine consistently demonstrated antidepressant-like effects in preclinical models and showed preliminary potential mechanisms of action. However, the limitations of current studies highlight the necessity for more comprehensive preclinical research and well-designed clinical trials.